FTIR characterization and microbiological application of polyoxometalates molybdic acid and potassium molybdate against MDR bacteria - Júlio César Silva; Letícia Rochele Oliveira da Silva; Dárcio Luiz de Sousa Júnior; Raimundo Luiz da Silva Pereira; Thiago Sampaio de Freitas; Cícera Laura Roque Paulo; Sheila Alves Gonçalves; Janaína Esmeraldo Rocha; João Arthur de Oliveira Borges; Henrique Douglas Melo Coutinho; Paulo de Tarso Cavalcante Freire; Francisco Ferreira de Sousa; et al. (Results in Chemistry, 2024)
The discovery of new antibiotics is a major challenge these days, as the emergence of resistant bacterial strains has intensified in recent years and the responsiveness of traditional drugs has been impaired, mainly due to their early use. As a way to overcome this current problem, studies to discover new drugs have intensified and among them are inorganic compounds. The objective of this work was to evaluate the direct antibacterial activity and combined with antibiotics ampicillin, ciprofloxacin and gentamicin of molybdic acid and potassium molybdate. Both compounds were chemically characterized and tested for their ability to inhibit the resistance mechanism presented by the Staphylococcus aureus (K-4100 e K-4414) strain, represented by the expression of the beta-lactamase enzyme. Microbiological tests were carried out using microdilution methodology with colorimetric development, using resazurin. Spectroscopic characterization was performed using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), for molybdic acid, a band located at 952 cm−1 was visualized, while for potassium molybdate the bands detected were located at 319 and 879 cm−1 The compounds did not show direct antibacterial activity, but acted to reinforce the effect of traditional antibiotics: ampicillin, ciprofloxacin and gentamicin, in different situations, against the bacteria Escherichia coli 06 and Staphylococcus aureus 10. Furthermore, the use of molybdates was promising in reversing the resistance mechanism of the bacterial strains Staphylococcus aureus K4100 and K4414. The results obtained are unprecedented for the molybdates tested and imply a better elucidation of the bioactivity of polyoxometalates and present new therapeutic possibilities through the use of molybdates. Toxicological tests and tests with other strains are encouraged through our research to better understand the activity of the compounds used.